Multifunctional posterior sclera reinforcing biological material with controllable mechanical and degradation properties and preparation method of multifunctional posterior sclera reinforcing biological material
By self-assembly and modifying the submucosal layer of the natural extracellular matrix scaffold, and building a multi-layer structure of photocrosslinked silk fibroin and sodium hyaluronate, the shortcomings of existing posterior scleral reinforcement materials in terms of biocompatibility, mechanical properties and degradation properties are solved, and the efficient posterior scleral reinforcement effect is achieved, providing new material options for the treatment of pathological high myopia.
Patent Information
- Application Number
- CN202411929979.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing posterior scleral reinforcement materials have shortcomings in terms of biocompatibility, mechanical properties and degradation properties, and it is difficult to effectively treat pathological high myopia.
The submucosal layer (SIS) of the natural extracellular matrix scaffold is modified by layer-by-layer self-assembly technology, and a photocrosslinked silk fibroin (SF) microgroove coating and sodium hyaluronate (SH) adhesion layer are constructed on its surface to prepare a multifunctional postscleral reinforcement biomaterial with high biocompatibility, controlled mechanics and degradation characteristics.
This material has excellent performance in biocompatibility, mechanical properties and degradation properties. It can effectively promote tissue regeneration and repair, significantly improve the reinforcement effect of the posterior sclera, and has the potential for clinical application.
Smart Images

Figure CN119701097A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomaterials, and in particular to a multifunctional posterior sclera reinforcement biomaterial with controllable mechanical and degradation properties and a preparation method thereof. Background Art
[0002] Pathological high myopia often causes a series of fundus degenerative lesions and reduced visual function. The sclera of patients with pathological high myopia becomes thinner and weaker, the production of proteoglycans and collagen (especially type I collagen) decreases, and the collagen fibers become thinner and disordered. These changes can easily lead to posterior scleral staphyloma under the action of intraocular pressure, and then cause complications such as macular degeneration, macular hole, retinoschisis or retinal detachment, and ultimately lead to irreversible vision loss or even blindness. Posterior scleral reinforcement (PSR) is to fix the reinforcement material to the posterior sclera, stimulate a series of beneficial inflammatory reactions in the local tissue, so that the reinforcement material and the posterior sclera fuse to form a new sclera with increased thickness and enhanced biomechanics, which can effectively shorten the axial length and reduce the incidence of intraocular complications. It is currently the most effective surgical method for the clinical treatment of pathological high myopia.
[0003] The selection of posterior scleral reinforcement materials has an important impact on the effect of PSR surgery. Reinforcement materials include biological materials and synthetic materials. Biological materials such as allogeneic sclera and bovine pericardium have good biocompatibility, but the source is insufficient and the supply of materials is limited. Artificial synthetic materials such as artificial pericardial patches and polyester fiber mesh, although widely available and easy to make in various sizes, often have low biocompatibility and safety, difficult to degrade, difficult to match biomechanics, and other problems. Therefore, it is urgent to develop a multifunctional reinforcement material with good biocompatibility and can simultaneously meet mechanical, degradation performance and tissue recovery.
[0004] The naturally derived extracellular matrix scaffold, the intestinal submucosa (SIS), has significant biological activity and can effectively promote tissue regeneration and repair. It has been widely used in experiments on various tissues such as the bladder, abdominal wall, skin, and dura mater. However, unfavorable factors such as rapid degradation in vivo and structural and mechanical instability have limited the further application of SIS. Silk fibroin (SF) in silkworm silk, as a natural crosslinker, can controllably adjust the mechanical properties and degradation rate of the material by changing the number of SF layers in the form of layer-by-layer self-assembly (LbL). Sodium hyaluronate (SH) was first discovered in the vitreous body of the eye. It has high viscoelasticity, hydrophilicity, and biocompatibility and is widely used in ophthalmic surgeries such as glaucoma and cataracts. At the same time, taking advantage of the advantages of SF and SH, a SF coating with directional grooves is constructed on the outside of the SIS membrane, and a SF-SH coating with high viscosity is constructed on the inner layer close to the sclera. A new multifunctional posterior scleral reinforcement biomaterial with high biocompatibility, controllable mechanical and degradation properties, and the ability to promote the regeneration of surrounding tissues is developed, which will be of great significance for the long-term, stable and effective treatment of pathological high myopia. Summary of the invention
[0005] In order to design a posterior sclera reinforcement biomaterial with controllable mechanical and degradation properties to achieve effective reinforcement of the posterior sclera, we prepared a photo-crosslinked SF (SFMA) microgroove coating with anisotropic characteristics on one side of the layer-by-layer self-assembled (LbL) SIS to guide cell arrangement and growth and promote tissue regeneration and repair; on the other side, a photo-crosslinked SF and sodium hyaluronate (SF-SH) mixed coating was prepared to improve biocompatibility and adhesion, realizing the preparation of a multifunctional posterior sclera reinforcement material (SFMA / LbL / SIS / SH) with controllable mechanical and degradation properties, which promoted the development and application of biomaterials in ophthalmic surgery.
[0006] The technical solution of the present invention is as follows:
[0007] A multifunctional biomaterial for posterior sclera reinforcement. In order to avoid the problem of insufficient structure and mechanical retention caused by rapid degradation of SIS during current clinical use, the SIS biomaterial with multifunctional coating uses SF LbL technology to modify SIS and prepare SIS membrane materials with controllable degradation and mechanical retention.
[0008] The preparation method of the SFMA / LbL / SIS / SH multifunctional posterior sclera reinforcement biomaterial of the present invention comprises the following steps:
[0009] (1) Preparation of SIS membrane: SIS was immersed in a mixed solution of methanol and chloroform (1:1, V / V) for 12 h, then digested in 0.05% trypsin at 37°C for 12 h, and then treated with 0.5% sodium dodecyl sulfate (SDS). The membrane was then immersed in 0.1% peracetic acid and freeze-dried to obtain a SIS membrane.
[0010] (2) Preparation of SF solution: 5 g of silkworm cocoons were placed in a boiling 0.02 M Na2CO3 solution for 1 h.
[0011] Then remove it, wash it in ultrapure water 5 times and dry it in a 45℃ oven for 24h.
[0012] The dried silk fibers were placed in a 9.3 M lithium bromide solution at 60 °C for 3 h until they were completely dissolved. The SF solution was then placed in a dialysis bag with a molecular weight cutoff of 3500 and dialyzed for 3 days.
[0013] After 1 day, the SF solution was centrifuged at 12000 rpm / min for 15 min to obtain a SF solution.
[0015] (3) Preparation of SF LbL surface functionalized SIS (denoted as SF / LbL / SIS): The SIS membrane was placed in a culture dish and an equal volume mixture of 1 mg / ml SF solution and 1 mg / ml methacrylylated SF (SilMA) solution was added. The mixture was shaken on a decolorizing shaker for 15 min, and then the SIS membrane was immersed in 90%
[0016] The solution was placed in methanol and finally dried with nitrogen to obtain SF / LbL / SIS modified with photocurable groups.
[0017] (4) Preparation of photocurable SF microgroove coating SIS (denoted as SFMA / LbL / SIS): 30 g of polydimethylsiloxane (PDMS) and 3 g of curing agent were weighed and mixed evenly on a silicon plate with a 20 μm wide microgroove.
[0018] , vacuum dried for 1 hour and then transferred to an 85°C oven for 4 hours.
[0019] The SFMA solution was dripped into the PET frame, and then the pre-soaked LbL SIS was placed into the solution.
[0020] The SFMA solution was solidified and irradiated with ultraviolet light for 35 seconds to form SFMA / LbL / SIS with a stable microgroove structure on the outside.
[0021] (5) Preparation of photocurable SH-SF adhesion coating SIS (denoted as SFMA / LbL / SIS / SH): 0.25%
[0022] The photoinitiator (LAP) was prepared with a mixed solution of 15 mg / ml photocurable SH and 5 mg / ml SilMA. 50 μL of the mixed solution was evenly applied to the inner surface of SFMA / LbL / SIS, irradiated with ultraviolet light for 8 seconds to cure it, and placed in a 37°C constant temperature box for slow drying to form a multifunctional SFMA / LbL / SIS / SH material.
[0023] Beneficial effects of the present invention: The synthesized SFMA LbL SIS SH has high stability, antibacterial properties, low toxicity and good biosafety. The multifunctional SFMA LbL SIS SH posterior scleral reinforcement biomaterial has high biocompatibility, controllable mechanical properties and degradation rate, good tissue integration ability and excellent adhesion, and can be used for clinical applications. In addition, the multifunctional SFMA LbL SIS SH posterior scleral reinforcement biomaterial is well integrated with the normal tissue around the defect, and the type I collagen on one side of the SFMA microgroove is directional. These results show that SFMA LbL SIS SH is a posterior scleral reinforcement biomaterial that has high biocompatibility, controllable mechanical and degradation properties to match the regeneration rate, and has great potential to improve the postoperative effect of PSR and promote the application of biomaterials in ophthalmic surgery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Surface morphology of SIS and SIS modified with different numbers of SF layers (a) Scanning electron microscopy (b) Confocal microscopy
[0025] Figure 2 Morphological characterization of SIS, SF / LbL / SIS, and SFMA / LbL / SIS (a) Scanning electron microscopy (b) 3D optical imaging
[0026] Figure 3 Analysis of mechanical retention of SIS and SF / LbL / SIS during enzymatic degradation (ac) Stress-strain curves of different membranes after 1, 3 and 7 days of enzymatic degradation (df) Statistics of stress, strain and Young's modulus of different membranes after 1, 3 and 7 days of enzymatic degradation
[0027] Figure 4 In vitro cytocompatibility evaluation of biomaterials (a) Cytoskeleton staining (b) CCK-8 analysis
[0028] Figure 5 Cell behavior analysis on biomaterial surfaces (a) Surface morphology of cytoskeleton (b) CCK-8 analysis (c) Immunofluorescence staining of type I collagen DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0030] Example 1: SIS membrane preparation
[0031] The SIS was immersed in a mixed solution of methanol and chloroform (1:1, V / V) for 12 h, followed by digestion in 0.05% trypsin at 37°C for 12 h, and then treated with 0.5% sodium dodecyl sulfate (SDS). The membrane was then immersed in 0.1% peracetic acid and freeze-dried to obtain the SIS membrane.
[0032] Example 2: Preparation of SF solution
[0033] 5g of silkworm cocoons were placed in a boiling 0.02M Na2CO3 solution for 1 hour, then removed, washed 5 times in ultrapure water and dried in a 45°C oven for 24 hours. The dried silk fibers were then placed in a 9.3M lithium bromide solution at 60°C for 3 hours until completely dissolved. The SF solution was then placed in a dialysis bag with a molecular weight cutoff of 3500 and dialyzed for 3 days. After 3 days, the SF solution was centrifuged at 12000rpm / min for 15 minutes to obtain the SF solution.
[0034] Example 3: Preparation of SF LbL surface functionalized SIS membrane (denoted as SF / LbL / SIS)
[0035] The SIS membrane was placed in a culture dish and an equal volume mixed solution of 1 mg / ml SF solution and 1 mg / ml methacryloyl SF (SilMA) solution was added. The membrane was shaken on a decolorizing shaker for 15 minutes. The SIS membrane was then immersed in a 90% methanol solution and finally dried with nitrogen to obtain SF / LbL / SIS modified with photocurable groups.
[0036] Example 4: Preparation of photocured SF microgroove coating SIS film (denoted as SFMA / LbL / SIS)
[0037] Weigh 30g of polydimethylsiloxane (PDMS) and 3g of curing agent, mix them evenly and pour them on a silicon plate with 20μm wide microgrooves, vacuum dry for 1h and then transfer to an 85℃ oven to dry for 4h. Pipette 120μLSFMA solution and drop it into the PET frame, then place the pre-soaked LbL SIS on the solution, and irradiate with ultraviolet light for 35s to cure the SFMA solution to form a stable microgroove structure SFMA / LbL / SIS.
[0038] Example 5: Preparation of double-sided SIS film with photocured SH-SF adhesion coating (denoted as SFMA / LbL / SIS / SH)
[0039] A mixed solution of 15 mg / ml photocurable SH and 5 mg / ml SilMA was prepared using 0.25% photoinitiator (LAP). 50 μL of the mixed solution was evenly applied to the upper surface of SFMA / LbL / SIS, irradiated with UV light for 8 seconds to cure it, and then placed in a 37°C thermostat for slow drying to form a double-layer functionalized SFMA / LbL / SIS / SH biomaterial.
[0040] Example 6: Mechanical retention of SF / LbL / SIS membranes
[0041] The tensile mechanical properties of SIS and SF / LbL / SIS membranes under enzyme degradation conditions were tested using a dynamic mechanical analyzer (DMA Q800). The samples were degraded in a collagenase (C0130, Sigma) solution. The samples were rinsed and dried naturally before testing, and then subjected to tensile testing. During the test, all samples were cut into rectangles with a length of 1 cm and a width of 2 mm. All tensile tests were carried out at room temperature with a test speed of 1.5 N / min, and stress-strain data were directly obtained from the testing machine based on the initial sample size. The tensile strength is the maximum stress at break, the fracture strain at break is the maximum strain value, and the elastic modulus of the membrane is calculated between 1-3% strain.
[0042] Example 7: In vitro cell compatibility of SFMA / LbL / SIS membrane
[0043] Mouse embryonic fibroblasts (NIH3T3) were used for in vitro cytocompatibility studies of the materials. Cell counting kit (CCK-8) was used to measure the proliferation of cells on SIS, SF / LbL / SIS, and SFMA / LbL / SIS. After 1, 3, and 7 days of co-culture of cells with materials, the culture medium was removed, and fresh culture medium containing 10% CCK-8 solution was added to each well. After reacting at 37°C for 1 hour, the absorbance of the supernatant at 450nm was measured using a spectrophotometer. Collagen I immunofluorescence staining was used to detect the arrangement of collagen matrix secreted by fibroblasts cultured on the membrane. After the cells were seeded on SIS, SF / LbL / SIS, and SFMA / LbL / SIS and cultured for 3 days, the cell samples were fixed with 4% paraformaldehyde for 30 minutes, then rinsed three times with PBS, and then treated with 0.2% Triton X-100 for 5 minutes at room temperature. After blocking with 2% bovine serum albumin for 2 hours, mouse anti-Collagen I (1:200) monoclonal antibody was added and incubated overnight at 4°C, washed with PBS, and fluorescent secondary antibody (goat anti-mouse IgG-Alexa Fluor 594, 1:300) was added and incubated at 37°C for 1 hour, and then washed with PBS. Finally, anti-fluorescence quenching mounting medium (containing DAPI) was used for sealing and observed and photographed with CLSM.
Claims
1. A multifunctional biomaterial for posterior sclera reinforcement, namely: a photo-crosslinked SF (SFMA) microgroove coating with anisotropic characteristics is prepared on one side of a layer-by-layer self-assembled (LbL) SIS, and a photo-crosslinked SF and sodium hyaluronate (SF-SH) mixed coating is prepared on the other side, to construct a multifunctional biomaterial (SFMA / LbL / SIS / SH) with controllable mechanical and degradation properties and high biocompatibility.
2. The preparation method of the multifunctional biomaterial for posterior sclera reinforcement according to claim 1 is: (1) Preparation of SIS membrane: SIS was immersed in a mixture of methanol and chloroform (1:1, V / V) for 12 h, then digested in 0.05% trypsin at 37°C for 12 h, and then treated with 0.5% sodium dodecyl sulfate (SDS). The membrane was then immersed in 0.1% peracetic acid and freeze-dried to obtain a SIS membrane; (2) Preparation of SF solution: 5 g of silkworm cocoons were placed in a boiling 0.02 M Na2CO3 solution for 1 hour, then removed, washed 5 times in ultrapure water and dried in a 45°C oven for 24 hours. The dried silk fibers were then placed in a 9.3 M lithium bromide solution at 60°C for 3 hours until completely dissolved. The SF solution was then placed in a dialysis bag with a molecular weight cutoff of 3500 and dialyzed for 3 days. After 3 days, the SF solution was centrifuged at 12000 rpm / min for 15 minutes to obtain the SF solution; (3) Preparation of SF LbL surface functionalized SIS (denoted as SF / LbL / SIS): Place the SIS membrane in a culture dish and add an equal volume mixed solution of 1 mg / ml SF solution and 1 mg / ml methacryloyl SF (SilMA) solution. Shake on a decolorizing shaker for 15 min. Then immerse the SIS membrane in 90% methanol solution. Finally, blow dry with nitrogen to obtain SF / LbL / SIS modified with photocurable groups. (4) Preparation of photocurable SF microgroove coating SIS (denoted as SFMA / LbL / SIS): Weigh 30g of polydimethylsiloxane (PDMS) and 3g of curing agent, mix them evenly and pour them on a silicon plate with 20μm wide microgrooves, vacuum dry for 1h and then transfer to an 85℃ oven to dry for 4h. Pipette 120μL of SFMA solution and drop it into the PET frame, then place the pre-soaked LbL SIS on the solution, and irradiate with ultraviolet light for 35s to cure the SFMA solution to form a SFMA / LbL / SIS with a stable microgroove structure on the outside; (5) Preparation of photocurable SH-SF adhesion coating SIS (denoted as SFMA / LbL / SIS / SH): A mixed solution of 15 mg / ml photocurable SH and 5 mg / ml SilMA was prepared using 0.25% photoinitiator (LAP). 50 μL of the mixed solution was evenly applied to the inner surface of SFMA / LbL / SIS, and then cured by ultraviolet light for 8 seconds. The material was then placed in a 37°C constant temperature box for slow drying to form a multifunctional SFMA / LbL / SIS / SH material.
3. The multifunctional biomaterial (SFMA / LbL / SIS / SH) for posterior sclera reinforcement as described in claim 1 has high biocompatibility and safety and can be used in clinical applications.
4. The multifunctional biomaterial (SFMA / LbL / SIS / SH) for posterior scleral reinforcement as described in claim 1 can achieve controllable mechanical and degradation properties, good tissue integration and adhesion, and has great potential for application in ophthalmic surgery.
Citation Information
Patent Citations
Fibroin three-dimensional bracket for nervus centralis remediation
CN106668950A
Soft tissue repair patch and preparation method thereof
CN109248341A
Preparation method of degradation healing promoting tissue repairing material
CN109939266A
Decellularized cartilage material from pig costal cartilage as well as preparation method and application of decellularized cartilage material
CN113599577A
Rapid light-cured laminin modified silk fibroin hydrogel as well as preparation method and application thereof
CN117106142A